Ammonia as an efficient COX-free hydrogen carrier: Fundamentals and feasibility analyses for fuel cell applications. (15th August 2018) - Cha, Junyoung; Jo, Young Suk; Jeong, Hyangsoo; Han, Jonghee; Nam, Suk Woo; Song, Kwang Ho; Yoon, Chang Won
Graphical abstract: Highlights: Pelletized Ru/La-Al2 O3 catalysts have superior NH3 dehydrogenation activity. The COx -free H2 generator is integrated to produce hydrogen on demand from NH3 . The H2 generator powers a 1 kW-class fuel cell without performance degradation. Reformer efficiency of >84% is achieved by recirculating H2 from a fuel cell. A potential H2 storage density of the system is ca. 7.0 wt% (system based). Abstract: A COX -free 1 kW-class hydrogen power pack fueled by liquid ammonia is presented. For applications in a practical-scale hydrogen production system in conjunction with a polymer electrolyte membrane fuel cell, Ru catalysts supported on La-doped alumina (Ru/La(x)-Al2 O3 ) were pelletized by varying the lanthanum doping content (x mol%) to control catalytic activities. An optimized Ru(1.06 wt%)/La(20)-Al2 O3 pellet catalyst presents a >99.7% conversion efficiency at 500 °C under a gas hourly space velocity of 5000 mL gcat −1 h −1 . Various materials were screened to remove residual ammonia from the product stream, and the X zeolite was chosen as a highly capable adsorbent. Based on the synthesized catalyst and screened adsorbent, a power pack consisting of a dehydrogenation reactor, an adsorbent tower, and a 1 kW-class polymer electrolyte membrane fuel cell was designed and manufactured. The as-integrated system can convert 9 L min −1 of ammonia into 13.4 L min −1 of hydrogen, powering a 1 kW-class fuel-cell continuously for >2 h without any performance degradation. To achieve autothermal and COX -free operations, heat required for ammonia dehydrogenation was provided by unutilized hydrogen from the fuel cell, drastically increasing the overall efficiency of the system to >49% while removing the external heat source, isobutane. Finally, a drone tethered to the system was operated, demonstrating the feasibility of an elongated flight time of >4 h, much longer than 14 min with Li-polymer battery loaded on the drone. The system is expected to meet the United States Department of Energy's 2020 gravimetric and volumetric hydrogen storage targets of 4.5 wt% and 30 gH2 L −1 at system weights of 43 kg and 50 kg, respectively.